THE EFFECT OF WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT BANK SULUTGO TOMOHON - Palar, Andika (Sam Ratulangi University, 2016)
The relationship between Job Satisfaction and Motivation have influence on employee performance in PT. Bank SulutGo Tbk Tomohon. This study aim to explain the simultan and partial effect of job satisfaction and work motivation on employee performance at PT. Bank SulutGo Tbk Tomohon. The population in this study were all employees at PT. Bank SulutGo Tbk Tomohon totaling 120 people, consisting of 76 men and 44 women. By using a purposive sampling method the sample is 80 respondents. Using multiple regression as a data analysis tool, this study found that job satisfaction and motivation have a significant effect on the performance of employees at PT. Bank SulutGo Tbk, Tomohon.